2012
DOI: 10.1007/s10437-012-9105-0
|View full text |Cite
|
Sign up to set email alerts
|

Private Business Investments in Heritage Sites in Tanzania: Recent Developments and Challenges for Heritage Management

Abstract: Private business investments in heritage sites in Tanzania have recently captured scholarly interest of some archaeologists. Curiosity in the matter has largely emanated from a fundamental need to widen the sites' utilization through heritage tourism. This paper reviews a recent incident in which a local community explicitly opposed the minister of Natural Resources and Tourism handing over ceremony of Kunduchi ruins site to a private investor. The paper also highlights recent developments, problems in private… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…In some cases, we encounter modern activities such as quarrying, construction, or cultivation that have exposed artifact-bearing layers. Several scholars have discussed the impacts of these contemporary economic activities on cultural heritage and archaeological sites in Tanzania (e.g., Bushozi 2014 ; Masele 2012 ).…”
Section: Survey Methodsmentioning
confidence: 99%
“…In some cases, we encounter modern activities such as quarrying, construction, or cultivation that have exposed artifact-bearing layers. Several scholars have discussed the impacts of these contemporary economic activities on cultural heritage and archaeological sites in Tanzania (e.g., Bushozi 2014 ; Masele 2012 ).…”
Section: Survey Methodsmentioning
confidence: 99%
“…This is unsurprising given that the potential and importance of MCH has not yet been fully realised anywhere in the world. Critically, MCH is under threat globally, and especially in the Western Indian Ocean, from natural forces and climate-driven coastal change as well as intensification in coastal and offshore development [54][55][56][57]. We are losing the resource before we have had a chance to harness its potential.…”
Section: The Challengementioning
confidence: 99%
“…The outcome was residents' rejection of conservation. Similarly, Hiyari (2012) and Masele (2012) studied participation in Al Salt City in Jordan and in Kunduchi Ruins in Tanzania, respectively, using the qualitative approach. They concluded that while non-participation causes residents to shun conservation activities, the promotion of genuine participation may cause them to support conservation.…”
Section: Influence Of Participation In Decision Making On Attitudes Towards Conservationmentioning
confidence: 99%